Instilling The Values of Religious Tolerance Through Multicultural Education in Social Studies Learning: Menanamkan Nilai-Nilai Toleransi Beragama Melalui Pendidikan Multikultural dalam Pembelajaran IPS - Siti Nuraeni, Ai; Tetep; Dianah, Lili (SAHUR Journal, 2022)
Multicultural education in a pluralistic society has an important role, because a pluralistic society is vulnerable to differences in conflict. This multicultural education needs to be applied at the school level as a start to prohibit tolerance for differences. Daya Susila Middle School is one of the schools that has a high level of diversity in its students both in terms of religion, ethnicity and customs, and culture. This study aims to reveal how to implementation of multicultural education in social studies learning and to find out the correlation between multicultural education on the embodiment of student values. The sample in this study was class VIII students at SMPS Daya Susila Garut by use a purposive sampling technique. Through a quantitative descriptive research approach, the research results show that the application of multicultural education to social studies learning that was oriented towards involving tolerance values ​​is very effectivelly, and the results of the correlational test show that there is a positive and strong correlation between multicultural education and the swelling of religious tolerance among students with a coefficient of determination of 66.3 % means it has a strong correlation. Thus that multicultural education is appropriate for use in schools with multiple students.